Síntese e caracterização de células solares de ZnO sensibilizadas por corante - Nunes, Vanja Fontenele (2018)
Solar cells are devices used for electricity conversion from solar energy through the photovoltaic effect. These devices still need to improve its stability and output, which motivates researches for materials and methods to solar cells (DSSC) set up. Zinc oxide is a semiconductor with advantages for dye sensitized solar cells applicability, such as good electronical mobility, transparency and stability. Electrodeposition is a simple method to the deposition and the fabrication of the cell. In this work, zinc oxide films were electrodeposited on transparent conductor oxide, controlling deposition parameters, such as, temperature and precursor concentration, and changing the potential deposition. The chosen applied potentials were -1.0, -1.2 and -1.4 V. The techniques used to characterize the films were scanning electron microscopy, x-ray and UV-Vis spectrophotometry, and, from the cells, it was obtained data such as open circuit voltage and short circuit current, besides its conversion efficiency. The DSSC assembled with the -1.4 V film presented better photovoltaic efficiency, 0.031%, besides 0.52 fill factor, 0.13 mA/cm2 of short-circuit current density and 8.87 kΩ/cm2 series resistance. The cell assembled with the -1.0 V photoanode film presented efficiency of 0.012%, 0.048 mA/cm2 of short-circuit current density and 1.38 kΩ/cm2 series resistance.